Six new species of Maesa (Primulaceae) from Papua New Guinea - Sumanon, Pirada; Eiserhardt, Wolf L.; Balslev, Henrik; Utteridge, Timothy M.a. (Phytotaxa, 2021)
Six new species of Maesa (Primulaceae-Maesoideae) from Papua New Guinea, namely M. angustibracteolata, M. aurulenta, M. brassii, M. oblanceolatifolia, M. pusilliflora and M. prolatifructa are described and illustrated based on observations from herbarium specimens; the taxonomic affinities of each species are also discussed.